2014
DOI: 10.1167/14.8.20
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the line: Estimations of line length in the Oppel-Kundt illusion

Abstract: In the Oppel-Kundt illusion, one of the oldest and least understood geometrical visual illusions, a line subdivided by a series of short orthogonal ticks appears longer than an identical line without these. Paradoxically, bisecting a long line with a single tick leads to perceived shortening of the line. We have systematically investigated the effects of adding 1 to 12 ticks on perceived line length and results suggest that at least three mechanisms must be at work: (a) bisection, which reduces perceived lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 23 publications
0
30
1
Order By: Relevance
“…Moreover, there was some evidence that the reversed pattern is also true: the inclusion of inner boundaries makes the object looks smaller. This finding seems in contrast to the "Helmholtz square illusion" or the "Oppel-Kundt illusion", according to which filled spaces appear larger than unfilled spaces (Mikellidou, & Thompson, 2014;Thompson & Mikellidou, 2011). However, this underestimation effect was not as large as the open-object illusion, and additional investigation is needed for establishing its robustness.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Moreover, there was some evidence that the reversed pattern is also true: the inclusion of inner boundaries makes the object looks smaller. This finding seems in contrast to the "Helmholtz square illusion" or the "Oppel-Kundt illusion", according to which filled spaces appear larger than unfilled spaces (Mikellidou, & Thompson, 2014;Thompson & Mikellidou, 2011). However, this underestimation effect was not as large as the open-object illusion, and additional investigation is needed for establishing its robustness.…”
Section: Discussionmentioning
confidence: 66%
“…Clearly, many important questions remained to be answered. For example, is the effect unique to objects or it is related to distorted space segmentation (e.g., Mikellidou & Thompson, 2014)? Can the effect be generalized to 3D or curved objects?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two different phases of the stimulus were used to prevent afterimages. To create prominent illusion, each rectangular stimulus consisted of seven lines, with a duty cycle of 0.9 (thin lines on a gray background) and a spatial frequency of 0.91 cycles/degree ( Mikellidou & Thompson, 2013 , 2014 ; Thompson & Mikellidou, 2011 ). We spatially jittered the stimuli by up to 0.1° to prevent afterimages providing cues to physical size changes between successive trials.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that a stimulus with a certain number of evenly allocated identical fillers induces a considerably stronger illusion than that with an irregular distribution (Lewis 1912, Noguchi 2003 or with many fillers fused into one continuous unit (Bailes 1995, Bertulis andBulatov 2001). At the same time, the region of the illusion maximum was relatively flat and varied between studies: the greatest effect was found for the number of fillers from 11 to 23 (Spiegel 1937), 9 to 14 (Piaget and Osterrieth 1953), 4 to 13 (Bulatov et al 1997), 11 to 13 (Wackermann and Kastner 2010), and 8 to 12 (Mikellidou and Thompson 2014). If the stimulus elements differed in shape or size then the effect of the illusion was substantially diminished (Obonai 1954, Wackermann and Kastner 2009, Wackermann 2012a.…”
Section: Introductionmentioning
confidence: 98%